Comparative Analysis of Sandcrete Hollow Blocks and Laterite Interlocking Blocks as Walling Elements - Raheem, Akeem Ayinde; Momoh, Ayodeji Kayode; Soyingbe, Aliu Adebayo (International Journal of Sustainable Construction Engineering and Technology, 2012)
This study considered the production and testing of sandcrete hollow blocks and laterite interlocking blocks with a view to comparing their physical characteristics and production cost. Some units of sandcrete hollow blocks and laterite interlocking blocks were made using machine vibrated sandcrete block mould and hydraulic interlocking block making machine respectively. The blocks were tested to determine their density and compressive strength. The results obtained from the tests were compared with the specifications of Nigerian Building and Road Research Institute (2006), Nigerian Building Code (2006), and Nigerian Industrial Standards (2000). The results indicated that the compressive strength of 225mm and 150mm sandcrete hollow blocks varies from 1.59 N/mm2 to 4.25 N/mm2 and 1.48N/mm2 to 3.35N/mm2 respectively, as the curing age increases from 7 to 28 days. For laterite interlocking blocks, the strength varies from 1.70N/mm2 at 7 days to 5.03N/mm2 at 28 days. All the blocks produced satisfied the minimum requirements in terms of compressive strength, by all available codes. The cost per square metre of 225mm and 150mm sandcrete hollow blocks are ₦2,808:00 and ₦2,340:00 respectively, while that of laterite interlocking blocks is ₦2,121:20.It was concluded that laterite interlocking blocks have better strength and are cheaper than sandcrete hollow blocks.